Kerentanan Wilayah Konflik dan Upaya Negara dalam Mengatasi Covid di Wilayah Konflik Asia - Gita Karisma; Khairunnisa Simbolon (Parahyangan Center for International Studies, 2023)
The Covid 19 pandemic has become an interesting issue contemporary, especially when the virus of Covid 19 spreads quickly throughout the world, then also spreads to the conflict areas. This phenomenon brings a concern when a country should be able to seriously overcome the pandemic problems, obviously getting involved into conflicts and clashes with certain ethnic groups or separatist groups. Using a qualitative method, this article looks at the state's trend on implementing its policy and dealing with Covid in the area of internal conflict particularly in Xinjiang and Rakhine. The neutrality of the state is tested in providing rights and ef orts to overcome the problem of Covid 19 pandemic. The discriminative and late responses of the States make it more complicated. The mitigation becomes even more difficult due to the vulnerability of conflict areas, which have long had problems of poverty, lack of infrastructures and health services, the existence of sentiment and distrust among each other. Keywords: Covid-19; policy; vulnerability; conflict; state